Preparing Modified Bonding Representations Inventory: Challenges and Solution - Pinaki Chowdhury (Indonesian Journal Of Educational Research and Review, 2021)
Collecting data on learners' performance in different chemistry contents and analysing them to identify their knowledge and understanding in related content areas is a major task of Chemistry Education Research. The data collection process on the learners' content knowledge and understanding of content knowledge requires a standard measuring tool. The preparation of standardized tools for measuring academic achievement requires computer software. All software used in the standardization of a tool comes at a cost and requires training for the researcher involved in handling the situation, which can impede the smooth running of a project. The same was the situation when the author was working on modifying the bonding representations inventory (BRI) for its local use in South Africa. The data analysis laboratory was situated in a different city, 500 km away from the researcher's field of work. Owing to the long distance and communication delay, the author was concerned with delays in the project. It is known that necessity, which can create an opportunity. The Microsoft Excel (MS-Excel) platform was used for standardizing the modified BRI because MS-Excel is available as a standard in MS-Office on the Windows platform. This paper presents a fact. That, a tool can be standardized by using MS-Excel without any complexity.